Attacks on Polish Bank Customers During the Pandemic: Cyberscams and the Role of Security Alerts - Kaczmarczyk, Wojciech (Journal of Finance and Financial Law, 2025)
The purpose of the article. The publication aims to determine the extent to which changes in the use of e-banking during the COVID-19 pandemic influenced the methods and scale of cyberscams in Europe (including Poland). Additionally, it seeks to assess whether Polish banks conducted a proper information policy and were able to practically implement the adopted solutions during the examined period. Methodology. First, an analysis of the available literature, applicable laws, and reports from state institutions was conducted. Then, security announcements from the five largest banks regarding cyberscams were examined. Additionally, a case study of three different incidents was carried out, including a review of complaint and court documentation. Results of the research. The study demonstrates the growth and expansion of banking cyber scams in Europe (including Poland) during the COVID-19 pandemic. The analysis of security alerts highlights the need for improvements in the actions taken. Additionally, the case study points to the existence of systemic and organizational shortcomings. These findings facilitated the identification of potential changes to reduce the scale of the phenomenon. The obtained results may be useful for both researchers and practitioners working in the banking or supervisory sector.